Outdoor sports fabric with antibacterial and anti-corrosion functions and production method thereof
By using modified antibacterial materials and anti-corrosion materials in sports fabrics, combined with porous coconut shell activated carbon particles and thermally expanded fibers, the problems of unstable antibacterial performance and poor breathability of existing fabrics are solved, and efficient antibacterial and anti-corrosion effects are achieved. And extend the service life of the fabric.
Patent Information
- Application Number
- CN202211487815.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-11-25
AI Technical Summary
During the use of existing sports fabrics, the antibacterial properties are difficult to stabilize, the breathability is poor, and the overall breathability is reduced after the corrosion-resistant coating is covered.
Porous coconut shell activated carbon particles are used as modified antibacterial materials, combined with tourmaline particles, far-infrared ceramic particles and carbonized wood particles as adsorption particles, and chitin fibers are used to seal the pores to improve adsorption and stability. At the same time, thermally expanded fibers and epoxy resin glue are used as anti-corrosion materials, and porous activated carbon particles are placed at both ends of the thermally expanded fibers to enhance breathability and anti-corrosion.
It achieves long-term antibacterial and anti-corrosion properties of the fabric, improves breathability and service life, and avoids the rapid decrease in antibacterial properties.
Smart Images

Figure CN116100902B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fabrics, and in particular relates to an outdoor sports fabric with antibacterial and anti-corrosion functions and a production method thereof. Background Art
[0002] With the development and progress of the times, the clothing industry has also been booming, and clothing fabrics are also colorful. Fabrics are materials used to make clothing. As one of the three elements of clothing, the performance of fabrics directly determines the quality of clothing.
[0003] Sportswear is mainly the clothing that people wear when doing sports or outdoor sports. Because athletes sweat a lot during exercise, sportswear must have better breathability, antibacterial and corrosion resistance. Antibacterial fabrics have good safety. They can effectively and completely remove bacteria, fungi and mold on fabrics, keep fabrics clean, and prevent bacterial regeneration and reproduction. Existing fabrics usually use tourmaline particles, far-infrared ceramic particles and activated carbon particles to improve the antibacterial properties of fabrics, but tourmaline particles, far-infrared ceramic particles and activated carbon particles are difficult to stably adhere to the inside of the fabric. With use, their antibacterial properties will be greatly reduced. In addition, corrosion-resistant fabrics are usually covered on one side with corrosion-resistant coatings, resulting in poor overall breathability of the fabrics. Summary of the invention
[0004] The purpose of the present invention is to provide an outdoor sports fabric with antibacterial and anti-corrosion functions and a production method thereof in order to solve the above problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] An outdoor sports fabric with antibacterial and anti-corrosion functions, comprising an inner and outer base layer, a modified antibacterial material arranged on the inner surface of the inner and outer base layers, and an anti-corrosion material arranged in the interlayer space between the inner and outer base layers;
[0007] The modified antibacterial material comprises porous coconut shell activated carbon particles, the internal pores of the porous coconut shell activated carbon particles are provided with adsorption particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitosan fibers containing cations;
[0008] The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles;
[0009] The anti-corrosion material comprises heat-expandable fibers and epoxy resin glue. Both ends of the heat-expandable fibers are provided with porous activated carbon particles. Russian Scotch pine particles are provided in the pores of the porous activated carbon particles.
[0010] As a further optimization scheme of the present invention, according to the mass percentage: the modified antibacterial material includes 50%-55% porous coconut shell activated carbon particles, 30%-35% adsorption particles, and 10%-20% chitosan fibers containing cations.
[0011] As a further optimization scheme of the present invention, in terms of mass percentage, the adsorption particles include 30%-40% tourmaline particles, 35%-45% far-infrared ceramic particles and 15%-35% carbonized wood particles.
[0012] As a further optimization scheme of the present invention, according to the mass percentage: the anti-corrosion material includes 15%-20% thermal expansion fiber, 10%-15% epoxy resin glue, 35%-45% porous activated carbon particles and 10%-40% Russian larch microparticles.
[0013] As a further optimization scheme of the present invention, the inner and outer base layers are formed by interlacing and weaving polyester fibers and cotton fibers.
[0014] As a further optimization solution of the present invention, the outer surfaces of the inner and outer base layers are provided with a waterproof coating.
[0015] As a further optimization scheme of the present invention, a method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions comprises the following steps:
[0016] S1: Preparation of adsorption particles;
[0017] Tourmaline, far-infrared ceramics and carbonized wood are taken as adsorption raw materials, and tourmaline particles, far-infrared ceramic particles and carbonized wood particles are obtained by ultra-fine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles;
[0018] S2: Preparation of modified antibacterial materials;
[0019] Adsorption particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension is added. After heating and stirring at 90-120° C. for 20-30 minutes, chitin fibers are added, and the mixture is stirred intermittently for multiple times in the manner of “stirring for 10 minutes and then standing for 5 minutes”, and anionic solution and polyvinylidene chloride are added. After heating and stirring at 80-100° C. for 15-25 minutes, the mixture is cooled at room temperature to obtain a semi-solidified gel-like modified antibacterial material;
[0020] S3: Preparation of anti-corrosion materials;
[0021] The mixed porous activated carbon particles and Russian larch microparticles are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated to form colloidal anticorrosive particles.
[0022] The pre-prepared colloidal anti-corrosion particles and the heat-expandable fibers are mixed and stirred at room temperature for 40-60 minutes to obtain an anti-corrosion material;
[0023] S4: Fabric-fabric composite preparation;
[0024] The semi-solidified gel-like modified antibacterial material is coated on the inner surface of the inner and outer base layers, and dried at 220-240°C for 10-15 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material reaches 6000-6500 MPa·s, the anti-corrosion material is placed in the interlayer space of the inner and outer base layers, and the temperature is 200-250°C, the pressure is 80-90 MPa, and intermittent pressurization is performed for 15-35 minutes to obtain the outdoor sports fabric with antibacterial and anti-corrosion functions.
[0025] As a further optimization scheme of the present invention, in step S1, the particle sizes of the tourmaline particles, far-infrared ceramic particles and carbonized wood particles are 2-5 μm, 3-4 μm and 1-3 μm respectively.
[0026] As a further optimization scheme of the present invention, in step S2, the stirring process is carried out in a high-pressure reactor and filled with inert gas.
[0027] The beneficial effects of the present invention are:
[0028] The present invention is provided with adsorption particles made of tourmaline particles, far-infrared ceramic particles and carbonized wood particles. The carbonized wood particles can adsorb odors and bacteria. The tourmaline particles and far-infrared ceramic particles can transfer far-infrared heat energy to the deeper part of the human body's subcutaneous tissue during outdoor sports. The generated warmth is radiated from the inside to the outside, so that the capillaries are dilated, blood circulation is promoted, and metabolism between various tissues is strengthened, which is convenient for people to use and plays an antibacterial and health-care role. The chitin fiber is used to block the pores of the porous coconut shell activated carbon particles, which not only improves the overall adsorption of the porous coconut shell activated carbon particles, but also effectively avoids the loss of adsorption particles inside the porous coconut shell activated carbon particles, thereby greatly extending the service life of the fabric.
[0029] The Russian larch microparticles provided in the present invention can effectively improve the overall corrosion resistance and adsorption properties of the porous activated carbon particles, and the porous activated carbon particles are placed at both ends of the thermal expansion fibers. When the thermal expansion fibers expand due to heat, the air permeability is enhanced and the cations in the porous activated carbon particles can be released for rapid adsorption on the modified antibacterial material 2 with anions, which not only ensures the contact between the coatings but also plays a role in air permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the main axonometric structure of the present invention;
[0031] Figure 2 It is a schematic diagram of the main axonometric structure of the anti-corrosion material of the present invention.
[0032] In the figure: 1. Inner and outer base layers; 2. Modified antibacterial material; 3. Anti-corrosion material; 31. Thermal expansion fiber; 32. Porous activated carbon particles; 33. Russian larch microparticles. DETAILED DESCRIPTION
[0033] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content. Example
[0034] like Figure 1 As shown, an outdoor sports fabric with antibacterial and anti-corrosion functions includes an inner and outer base layer 1, a modified antibacterial material 2 arranged on the inner surface of the inner and outer base layer 1, and an anti-corrosion material 3 arranged in the interlayer space between the inner and outer base layers 1;
[0035] The modified antibacterial material 2 comprises porous coconut shell activated carbon particles, the internal pores of the porous coconut shell activated carbon particles are provided with adsorption particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitosan fibers containing cations; wherein, in terms of mass percentage: the modified antibacterial material 2 comprises 50% porous coconut shell activated carbon particles, 30% adsorption particles, and 20% chitosan fibers containing cations.
[0036] The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles; wherein, by mass percentage: the adsorption particles include 30% tourmaline particles, 35% far-infrared ceramic particles and 35% carbonized wood particles.
[0037] like Figure 2As shown, the anti-corrosion material 3 includes heat-expandable fibers 31 and epoxy resin glue. Both ends of the heat-expandable fibers 31 are provided with porous activated carbon particles 32 . Russian larch particles 33 are provided in the pores of the porous activated carbon particles 32 .
[0038] Wherein, in terms of mass percentage, the anti-corrosion material 3 includes 15% of thermal expansion fiber 31 , 10% of epoxy resin glue, 35% of porous activated carbon particles 32 and 40% of Russian Scotch pine particles 33 .
[0039] The inner and outer base layers 1 are formed by interlacing and weaving polyester fibers and cotton fibers.
[0040] The outer surfaces of the inner and outer base layers 1 are provided with a waterproof coating.
[0041] A method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions, the production method comprising the following steps:
[0042] S1: Preparation of adsorption particles;
[0043] Tourmaline, far-infrared ceramics and carbonized wood are taken as adsorption raw materials, and tourmaline particles with a particle size range of 2 μm, far-infrared ceramic particles of 3 μm and carbonized wood particles of 1 μm are obtained through ultra-fine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles;
[0044] S2: Preparation of modified antibacterial material 2;
[0045] Adsorption particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension agent is added. Inert gas is injected into a high-pressure reactor, and the mixture is heated and stirred at 90°C for 20 minutes. Chitosan fibers are added, and the mixture is stirred intermittently for multiple times in the manner of "stirring for 10 minutes and then standing for 5 minutes". Anionic solution and polyvinylidene chloride are added, and the mixture is heated and stirred at 80°C for 15 minutes, and then cooled at room temperature to obtain a semi-solidified gel-like modified antibacterial material 2.
[0046] S3: preparation of anti-corrosion material 3;
[0047] The mixed porous activated carbon particles 32 and Russian larch microparticles 33 are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated and form colloidal anticorrosive particles.
[0048] The pre-prepared colloid anti-corrosion particles and the heat-expandable fibers 31 are mixed and stirred at room temperature for 40 minutes to obtain an anti-corrosion material 3;
[0049] S4: Fabric-fabric composite preparation;
[0050] The semi-solidified gel-like modified antibacterial material 2 is coated on the inner surface of the inner and outer base layers 1 and dried at 220°C for 10 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material 2 reaches 6000MPa·s, the anti-corrosion material 3 is placed in the interlayer space of the inner and outer base layers 1. The temperature is 200°C and the pressure is 80MPA. After intermittent pressurization for 15 minutes, the outdoor sports fabric with antibacterial and anti-corrosion functions is obtained. Example
[0051] like Figure 1 As shown, an outdoor sports fabric with antibacterial and anti-corrosion functions includes an inner and outer base layer 1, a modified antibacterial material 2 arranged on the inner surface of the inner and outer base layer 1, and an anti-corrosion material 3 arranged in the interlayer space between the inner and outer base layers 1;
[0052] The modified antibacterial material 2 comprises porous coconut shell activated carbon particles, the internal pores of the porous coconut shell activated carbon particles are provided with adsorption particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitosan fibers containing cations; wherein, by mass percentage: the modified antibacterial material 2 comprises 53% porous coconut shell activated carbon particles, 32% adsorption particles, and 10% chitosan fibers containing cations.
[0053] The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles; wherein, by mass percentage: the adsorption particles include 35% tourmaline particles, 40% far-infrared ceramic particles and 25% carbonized wood particles.
[0054] like Figure 2 As shown, the anti-corrosion material 3 includes heat-expandable fibers 31 and epoxy resin glue. Both ends of the heat-expandable fibers 31 are provided with porous activated carbon particles 32 . Russian larch particles 33 are provided in the pores of the porous activated carbon particles 32 .
[0055] Wherein, in terms of mass percentage, the anti-corrosion material 3 includes 18% of thermal expansion fibers 31 , 12% of epoxy resin glue, 40% of porous activated carbon particles 32 and 30% of Russian Scots pine particles 33 .
[0056] The inner and outer base layers 1 are formed by interlacing and weaving polyester fibers and cotton fibers.
[0057] The outer surfaces of the inner and outer base layers 1 are provided with a waterproof coating.
[0058] A method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions, the production method comprising the following steps:
[0059] S1: Preparation of adsorption particles;
[0060] Tourmaline, far-infrared ceramics and carbonized wood are used as adsorption raw materials. Tourmaline particles with a particle size range of 3 μm, far-infrared ceramic particles of 3.5 μm and carbonized wood particles of 2 μm are obtained through ultrafine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles.
[0061] S2: Preparation of modified antibacterial material 2;
[0062] Adsorption particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension is added. Inert gas is injected into a high-pressure reactor, and after heating and stirring at 100°C for 25 minutes, chitin fibers are added, and the method of "stirring for 10 minutes and then standing for 5 minutes" is adopted, and intermittent stirring is performed for multiple times, and anion solution and polyvinylidene chloride are added, and after heating and stirring at 90°C for 20 minutes, it is cooled at room temperature to obtain a semi-solidified gel-like modified antibacterial material 2;
[0063] S3: preparation of anti-corrosion material 3;
[0064] The mixed porous activated carbon particles 32 and Russian larch microparticles 33 are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated and form colloidal anticorrosive particles.
[0065] The pre-prepared colloid anti-corrosion particles and the heat-expandable fibers 31 are mixed and stirred at room temperature for 50 minutes to obtain an anti-corrosion material 3;
[0066] S4: Fabric-fabric composite preparation;
[0067] The semi-solidified gel-like modified antibacterial material 2 is coated on the inner surface of the inner and outer base layers 1 and dried at 230°C for 13 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material 2 reaches 6200 MPa·s, the anti-corrosion material 3 is placed in the interlayer space of the inner and outer base layers 1. The temperature is 230°C and the pressure is 85 MPa. After intermittent pressurization for 20 minutes, the outdoor sports fabric with antibacterial and anti-corrosion functions is obtained. Example
[0068] like Figure 1 As shown, an outdoor sports fabric with antibacterial and anti-corrosion functions includes an inner and outer base layer 1, a modified antibacterial material 2 arranged on the inner surface of the inner and outer base layer 1, and an anti-corrosion material 3 arranged in the interlayer space between the inner and outer base layers 1;
[0069] The modified antibacterial material 2 comprises porous coconut shell activated carbon particles, the internal pores of the porous coconut shell activated carbon particles are provided with adsorption particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitosan fibers containing cations; wherein, in terms of mass percentage: the modified antibacterial material 2 comprises 55% porous coconut shell activated carbon particles, 35% adsorption particles, and 10% chitosan fibers containing cations.
[0070] The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles; wherein, by mass percentage: the adsorption particles include 40% tourmaline particles, 45% far-infrared ceramic particles and 15% carbonized wood particles.
[0071] like Figure 2 As shown, the anti-corrosion material 3 includes heat-expandable fibers 31 and epoxy resin glue. Both ends of the heat-expandable fibers 31 are provided with porous activated carbon particles 32 . Russian larch particles 33 are provided in the pores of the porous activated carbon particles 32 .
[0072] Wherein, in terms of mass percentage, the anti-corrosion material 3 includes 20% of thermal expansion fibers 31 , 15% of epoxy resin glue, 45% of porous activated carbon particles 32 and 20% of Russian Scots pine particles 33 .
[0073] The inner and outer base layers 1 are formed by interlacing and weaving polyester fibers and cotton fibers.
[0074] The outer surfaces of the inner and outer base layers 1 are provided with a waterproof coating.
[0075] A method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions, the production method comprising the following steps:
[0076] S1: Preparation of adsorption particles;
[0077] Tourmaline, far-infrared ceramics and carbonized wood are taken as adsorption raw materials, and tourmaline particles with a particle size range of 5 μm, far-infrared ceramic particles with a particle size range of 4 μm and carbonized wood particles with a particle size range of 3 μm are obtained through ultra-fine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles;
[0078] S2: Preparation of modified antibacterial material 2;
[0079] Adsorption particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension is added. Inert gas is injected into a high-pressure reactor, and after heating and stirring at 120°C for 30 minutes, chitin fibers are added, and the method of "stirring for 10 minutes and then standing for 5 minutes" is adopted, and intermittent stirring is performed for multiple times, and anion solution and polyvinylidene chloride are added. After heating and continuous stirring at 100°C for 25 minutes, it is cooled at room temperature to obtain a semi-solidified gel-like modified antibacterial material 2;
[0080] S3: preparation of anti-corrosion material 3;
[0081] The mixed porous activated carbon particles 32 and Russian larch microparticles 33 are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated and form colloidal anticorrosive particles.
[0082] The pre-prepared colloid anti-corrosion particles and the heat-expandable fibers 31 are mixed and stirred at room temperature for 60 minutes to obtain an anti-corrosion material 3;
[0083] S4: Fabric-fabric composite preparation;
[0084] The semi-solidified gel-like modified antibacterial material 2 is coated on the inner surface of the inner and outer base layers 1 and dried at 240°C for 15 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material 2 reaches 6500MPa·s, the anti-corrosion material 3 is placed in the interlayer space of the inner and outer base layers 1. The temperature is 250°C and the pressure is 90MPA. After intermittent pressurization for 35 minutes, the outdoor sports fabric with antibacterial and anti-corrosion functions is obtained.
[0085] Comparative Example 1
[0086] like Figure 1 As shown, an outdoor sports fabric with antibacterial and anti-corrosion functions includes an inner and outer base layer 1, a modified antibacterial material 2 arranged on the inner surface of the inner and outer base layer 1, and an anti-corrosion material 3 arranged in the interlayer space between the inner and outer base layers 1;
[0087] The modified antibacterial material 2 comprises porous coconut shell activated carbon particles, the internal pores of the porous coconut shell activated carbon particles are provided with adsorption particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitosan fibers containing cations; wherein, in terms of mass percentage: the modified antibacterial material 2 comprises 55% porous coconut shell activated carbon particles, 35% adsorption particles, and 10% chitosan fibers containing cations.
[0088] The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles; wherein, by mass percentage: the adsorption particles include 40% tourmaline particles, 45% far-infrared ceramic particles and 15% carbonized wood particles.
[0089] like Figure 2 As shown, the anti-corrosion material 3 includes heat-expandable fibers 31 and epoxy resin glue. Both ends of the heat-expandable fibers 31 are provided with porous activated carbon particles 32 . Russian larch particles 33 are provided in the pores of the porous activated carbon particles 32 .
[0090] Wherein, in terms of mass percentage, the anti-corrosion material 3 includes 20% of thermal expansion fibers 31 , 15% of epoxy resin glue, 45% of porous activated carbon particles 32 and 20% of Russian Scots pine particles 33 .
[0091] The inner and outer base layers 1 are formed by interlacing and weaving polyester fibers and cotton fibers.
[0092] The outer surfaces of the inner and outer base layers 1 are provided with a waterproof coating.
[0093] A method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions, the production method comprising the following steps:
[0094] S1: Preparation of adsorption particles;
[0095] Tourmaline, far-infrared ceramics and carbonized wood are taken as adsorption raw materials. Tourmaline particles with a particle size of 10 μm, far-infrared ceramic particles with a particle size of 16 μm and carbonized wood particles with a particle size of 19 μm are obtained through ultrafine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles.
[0096] S2: Preparation of modified antibacterial material 2;
[0097] Adsorption particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension is added. Inert gas is injected into a high-pressure reactor, and after heating and stirring at 120°C for 30 minutes, chitin fibers are added, and the method of "stirring for 10 minutes and then standing for 5 minutes" is adopted, and intermittent stirring is performed for multiple times, and anion solution and polyvinylidene chloride are added. After heating and continuous stirring at 100°C for 25 minutes, it is cooled at room temperature to obtain a semi-solidified gel-like modified antibacterial material 2;
[0098] S3: preparation of anti-corrosion material 3;
[0099] The mixed porous activated carbon particles 32 and Russian larch microparticles 33 are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated and form colloidal anticorrosive particles.
[0100] The pre-prepared colloid anti-corrosion particles and the heat-expandable fibers 31 are mixed and stirred at room temperature for 60 minutes to obtain an anti-corrosion material 3;
[0101] S4: Fabric-fabric composite preparation;
[0102] The semi-solidified gel-like modified antibacterial material 2 is coated on the inner surface of the inner and outer base layers 1 and dried at 240°C for 15 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material 2 reaches 6500MPa·s, the anti-corrosion material 3 is placed in the interlayer space of the inner and outer base layers 1. The temperature is 250°C and the pressure is 90MPA. After intermittent pressurization for 35 minutes, the outdoor sports fabric with antibacterial and anti-corrosion functions is obtained.
[0103] Comparative Example 2
[0104] like Figure 1 As shown, an outdoor sports fabric with antibacterial and anti-corrosion functions includes an inner and outer base layer 1, a modified antibacterial material 2 arranged on the inner surface of the inner and outer base layer 1, and an anti-corrosion material 3 arranged in the interlayer space between the inner and outer base layers 1;
[0105] The modified antibacterial material 2 comprises porous coconut shell activated carbon particles, the internal pores of the porous coconut shell activated carbon particles are provided with adsorption particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitosan fibers containing cations; wherein, in terms of mass percentage: the modified antibacterial material 2 comprises 55% porous coconut shell activated carbon particles, 35% adsorption particles, and 10% chitosan fibers containing cations.
[0106] The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles; wherein, by mass percentage: the adsorption particles include 40% tourmaline particles, 45% far-infrared ceramic particles and 15% carbonized wood particles.
[0107] like Figure 2 As shown, the anti-corrosion material 3 includes heat-expandable fibers 31 and epoxy resin glue. Both ends of the heat-expandable fibers 31 are provided with porous activated carbon particles 32 . Russian larch particles 33 are provided in the pores of the porous activated carbon particles 32 .
[0108] Wherein, in terms of mass percentage, the anti-corrosion material 3 includes 20% of thermal expansion fibers 31 , 15% of epoxy resin glue, 45% of porous activated carbon particles 32 and 20% of Russian Scots pine particles 33 .
[0109] The inner and outer base layers 1 are formed by interlacing and weaving polyester fibers and cotton fibers.
[0110] The outer surfaces of the inner and outer base layers 1 are provided with a waterproof coating.
[0111] A method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions, the production method comprising the following steps:
[0112] S1: Preparation of adsorption particles;
[0113] Tourmaline, far-infrared ceramics and carbonized wood are taken as adsorption raw materials, and tourmaline particles with a particle size range of 5 μm, far-infrared ceramic particles with a particle size range of 4 μm and carbonized wood particles with a particle size range of 3 μm are obtained through ultra-fine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles;
[0114] S2: Preparation of modified antibacterial material 2;
[0115] Adsorbent particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension is added, an inert gas is injected into a high-pressure reactor, and after heating and stirring at 120° C. for 30 minutes, chitin fibers are added, and stirring is continued for several times, and anion solution and polyvinylidene chloride are added, and after heating and stirring at 100° C. for 25 minutes, cooling at room temperature is performed to obtain a semi-solidified gel-like modified antibacterial material 2;
[0116] S3: preparation of anti-corrosion material 3;
[0117] The mixed porous activated carbon particles 32 and Russian larch microparticles 33 are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated and form colloidal anticorrosive particles.
[0118] The pre-prepared colloid anti-corrosion particles and the heat-expandable fibers 31 are mixed and stirred at room temperature for 60 minutes to obtain an anti-corrosion material 3;
[0119] S4: Fabric-fabric composite preparation;
[0120] The semi-solidified gel-like modified antibacterial material 2 is coated on the inner surface of the inner and outer base layers 1, and dried at 240°C for 15 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material 2 reaches 6500MPa·s, the anti-corrosion material 3 is placed in the interlayer space of the inner and outer base layers 1, and the temperature is 250°C, the pressure is 90MPA, and the intermittent pressurization is performed for 35 minutes to obtain the outdoor sports fabric with antibacterial and anti-corrosion functions.
[0121] Comparative Example 3
[0122] like Figure 1 As shown, an outdoor sports fabric with antibacterial and anti-corrosion functions includes an inner and outer base layer 1, a modified antibacterial material 2 arranged on the inner surface of the inner and outer base layer 1, and an anti-corrosion material 3 arranged in the interlayer space between the inner and outer base layers 1;
[0123] The modified antibacterial material 2 comprises porous coconut shell activated carbon particles, the internal pores of the porous coconut shell activated carbon particles are provided with adsorption particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitosan fibers containing cations; wherein, in terms of mass percentage: the modified antibacterial material 2 comprises 55% porous coconut shell activated carbon particles, 35% adsorption particles, and 10% chitosan fibers containing cations.
[0124] The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles; wherein, by mass percentage: the adsorption particles include 40% tourmaline particles, 45% far-infrared ceramic particles and 15% carbonized wood particles.
[0125] like Figure 2 As shown, the anti-corrosion material 3 includes heat-expandable fibers 31 and epoxy resin glue. Both ends of the heat-expandable fibers 31 are provided with porous activated carbon particles 32 . Russian larch particles 33 are provided in the pores of the porous activated carbon particles 32 .
[0126] Wherein, in terms of mass percentage, the anti-corrosion material 3 includes 20% of thermal expansion fibers 31 , 15% of epoxy resin glue, 45% of porous activated carbon particles 32 and 20% of Russian Scots pine particles 33 .
[0127] The inner and outer base layers 1 are formed by interlacing and weaving polyester fibers and cotton fibers.
[0128] The outer surfaces of the inner and outer base layers 1 are provided with a waterproof coating.
[0129] A method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions, the production method comprising the following steps:
[0130] S1: Preparation of adsorption particles;
[0131] Tourmaline, far-infrared ceramics and carbonized wood are taken as adsorption raw materials, and tourmaline particles with a particle size range of 5 μm, far-infrared ceramic particles with a particle size range of 4 μm and carbonized wood particles with a particle size range of 3 μm are obtained through ultra-fine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles;
[0132] S2: Preparation of modified antibacterial material 2;
[0133] Adsorption particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension is added. Inert gas is injected into a high-pressure reactor, and after heating and stirring at 120°C for 30 minutes, chitin fibers are added, and the method of "stirring for 10 minutes and then standing for 5 minutes" is adopted, and intermittent stirring is performed for multiple times, and anion solution and polyvinylidene chloride are added. After heating and continuous stirring at 100°C for 25 minutes, it is cooled at room temperature to obtain a semi-solidified gel-like modified antibacterial material 2;
[0134] S3: preparation of anti-corrosion material 3;
[0135] The mixed porous activated carbon particles 32 and Russian larch microparticles 33 are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated and form colloidal anticorrosive particles.
[0136] The pre-prepared colloid anti-corrosion particles and the heat-expandable fibers 31 are mixed and stirred at room temperature for 60 minutes to obtain an anti-corrosion material 3;
[0137] S4: Fabric-fabric composite preparation;
[0138] The semi-solidified gel-like modified antibacterial material 2 is coated on the inner surface of the inner and outer base layers 1 and dried at 240°C for 15 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material 2 reaches 1500MPa·s, the anti-corrosion material 3 is placed in the interlayer space of the inner and outer base layers 1. The temperature is 250°C and the pressure is 90MPA. After intermittent pressurization for 35 minutes, the outdoor sports fabric with antibacterial and anti-corrosion functions is obtained.
[0139] Experiment 1:
[0140] Antibacterial performance test was carried out for Examples 1-3 and Comparative Examples 1-3. A 10 cm² seamless down jacket fabric was taken as the first sample fabric, and the front and back sides were marked on the first sample fabric. The back side of the first sample fabric was laid flat on a culture dish containing bacteria (Staphylococcus aureus, Candida albicans and Escherichia coli), and the first sample fabric was fixed at the opening of the culture dish using a hoop, and was placed in an incubator at a humidity of 10% and a temperature of 25°C for 30 minutes. The bacterial content on the front and back sides of the first sample fabric was measured by a bacteria sampler of model JCQ-4 to evaluate the antibacterial performance of the seamless down jacket fabric. The specific test results are as follows:
[0141] ;
[0142] Table 1
[0143] According to the analysis in Table 1, since the reverse side of the first sample material directly contacts the bacteria in the culture dish, the bacterial content value of the front side of the outdoor sports fabric obtained by the antibacterial performance test is slightly smaller than the bacterial content value of the reverse side, and the antibacterial performance of the sample fabrics in Examples 1-3 is significantly better than that of the sample fabrics in Comparative Examples 1-4. The reason is that the adsorption particles made of tourmaline particles, far-infrared ceramic particles and carbonized wood particles, the carbonized wood particles can adsorb odor and bacteria, and the tourmaline particles and far-infrared ceramic particles can transfer far-infrared heat energy to the deeper part of the human body under the skin during outdoor sports. The generated warmth is radiated from the inside to the outside, so that the capillaries are dilated, blood circulation is promoted, and metabolism between various tissues is strengthened, which is convenient for people to use and plays an antibacterial and health-care role. The chitin fiber is used to block the pores of the porous coconut shell activated carbon particles, which not only improves the overall adsorption of the porous coconut shell activated carbon particles, but also effectively avoids the loss of adsorption particles inside the porous coconut shell activated carbon particles, thereby extending the service life of the fabric.
[0144] Experiment 2:
[0145] For Example 1-3 and Comparative Example 1-3, the anti-corrosion performance test was carried out, and a seamless down jacket fabric with a thickness of 3 mm was taken as the second sample fabric, and the reverse side of the second sample fabric was laid flat on a beaker filled with ethyl acetate solution, and the second sample fabric was fixed at the opening of the beaker with a hoop, and the beaker was inverted and left to stand for 10 minutes. The damaged thickness of the second sample fabric was measured using a thickness gauge. The specific test results are as follows:
[0146] ;
[0147] Table 2
[0148] Through the analysis of Table 2, it can be concluded that the anti-corrosion performance of the sample fabrics in Examples 1-3 is significantly better than that of the sample fabrics in Comparative Examples 1-4. The reason is that the Russian larch microparticles can improve the overall corrosion resistance and adsorption of the porous activated carbon particles, and the porous activated carbon particles are placed at both ends of the thermal expansion fiber. When the thermal expansion fiber is heated and expanded, the air permeability is enhanced and the cations in the porous activated carbon particles can be released for rapid adsorption on the modified antibacterial material 2 with anions, which not only ensures the contact between the coatings, but also effectively plays a role in air permeability.
[0149] By comparing the experimental results in Experiment 1 and Experiment 2, we can conclude that:
[0150] In Comparative Example 1, the particle sizes of tourmaline particles, far-infrared ceramic particles and carbonized wood particles were modified to 10μm, 16μm and 19μm, respectively, resulting in the tourmaline particles, far-infrared ceramic particles and carbonized wood particles not completely entering the internal pores of the porous coconut shell activated carbon particles, causing poor adsorption effect of the porous coconut shell activated carbon particles. Therefore, the antibacterial property of the first sample fabric is greatly reduced, while the anti-corrosion effect of the second sample fabric is slightly reduced.
[0151] In comparative example 2, the intermittent stirring mode of "stirring for 10 minutes and then standing for 5 minutes" was changed to continuous stirring. Excessive stirring would cause the tourmaline particles, far-infrared ceramic particles and carbonized wood particles to separate from the internal pores of the porous coconut shell activated carbon particles, and it would be difficult to ensure the adsorption between the chitin fibers and the porous coconut shell activated carbon particles. Therefore, the antibacterial property of the first sample fabric was slightly reduced, while the anti-corrosion effect of the second sample fabric was slightly reduced.
[0152] In Comparative Example 3, the viscosity of the modified antibacterial material 2 is reduced to 1500 MPa·s. The reduced viscosity of the modified antibacterial material 2 will lead to poor bonding strength between the modified antibacterial material 2 and the anti-corrosion material 3, causing dislocation of the anti-corrosion material 3 and loss of effective ingredients of the anti-corrosion material 3. Therefore, the antibacterial property of the first sample fabric is reduced, while the anti-corrosion effect of the second sample fabric is greatly reduced.
[0153] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for producing outdoor sports fabrics with antibacterial and anti-corrosion functions, characterized in that: The outdoor sports fabric comprises an inner and outer base layer, a modified antibacterial material arranged on the inner surface of the inner and outer base layers, and an anti-corrosion material arranged in the interlayer space between the inner and outer base layers; The modified antibacterial material comprises porous coconut shell activated carbon particles, adsorption particles are arranged in the internal pores of the porous coconut shell activated carbon particles, and the outer surface of the porous coconut shell activated carbon particles is wrapped with chitin fibers containing cations; in terms of mass percentage: the modified antibacterial material comprises 50%-55% porous coconut shell activated carbon particles, 30%-35% adsorption particles, and 10%-20% chitin fibers containing cations; The adsorption particles include tourmaline particles, far-infrared ceramic particles and carbonized wood particles; in terms of mass percentage: the adsorption particles include 30%-40% tourmaline particles, 35%-45% far-infrared ceramic particles and 15%-35% carbonized wood particles; The anti-corrosion material comprises heat-expandable fiber and epoxy resin glue, both ends of the heat-expandable fiber are provided with porous activated carbon particles, and the pores of the porous activated carbon particles are provided with Russian Scots pine microparticles; in terms of mass percentage: the anti-corrosion material comprises 15%-20% heat-expandable fiber, 10%-15% epoxy resin glue, 35%-45% porous activated carbon particles and 10%-40% Russian Scots pine microparticles; The steps of the production method include: S1: Preparation of adsorption particles; Tourmaline, far-infrared ceramics and carbonized wood are taken as adsorption raw materials, and tourmaline particles, far-infrared ceramic particles and carbonized wood particles are obtained by ultrafine grinding technology. A certain proportion of tourmaline particles, far-infrared ceramic particles and carbonized wood particles are quantitatively added and uniformly mixed to obtain adsorption particles; the particle sizes of the tourmaline particles, far-infrared ceramic particles and carbonized wood particles are 2-5μm, 3-4μm and 1-3μm respectively; S2: Preparation of modified antibacterial materials; Adsorption particles and porous coconut shell activated carbon particles are taken as mixed raw materials, and a water suspension is added. After heating and stirring at 90-120° C. for 20-30 minutes, chitin fibers are added, and the mixture is stirred for 10 minutes and then allowed to stand for 5 minutes. The mixture is stirred intermittently for multiple times. Anionic solution and polyvinylidene chloride are added, and the mixture is heated at 80-100° C. and stirred continuously for 15-25 minutes, and then cooled at room temperature to obtain a semi-solidified gel-like modified antibacterial material. S3: Preparation of anti-corrosion materials; The mixed porous activated carbon particles and Russian larch microparticles are used as the material to be coated, epoxy resin glue is used as the coating material, and mutually immiscible organic solvents are used as the coating material dissolving agent and precipitation agent. The reverse dripping interface film-forming technology is used to coat the epoxy resin glue on the outer surface of the material to be coated to form colloidal anticorrosive particles. The above-mentioned colloid anti-corrosion particles and heat-expandable fibers are mixed, and stirred at room temperature for 40-60 minutes to obtain an anti-corrosion material; S4: fabric composite preparation; The semi-solidified gel-like modified antibacterial material is coated on the inner surface of the inner and outer base layers, and dried at 220-240°C for 10-15 minutes. When the viscosity of the semi-solidified gel-like modified antibacterial material reaches 6000-6500 MPa·s, the anti-corrosion material is placed in the interlayer space of the inner and outer base layers, and the temperature is 200-250°C, the pressure is 80-90 MPa, and intermittent pressurization is performed for 15-35 minutes to obtain the outdoor sports fabric with antibacterial and anti-corrosion functions.
2. The method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions according to claim 1, characterized in that: The inner and outer base layers are formed by interlaced weaving of polyester fibers and cotton fibers.
3. The method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions according to claim 1, characterized in that: The outer surfaces of the inner and outer base layers are provided with a waterproof coating.
4. The method for producing an outdoor sports fabric with antibacterial and anti-corrosion functions according to claim 1, characterized in that: In step S2, the stirring is performed in a high-pressure reactor and filled with inert gas.
Citation Information
Patent Citations
Method for coating powdery material with high polymer material
CN105384592A
Deodorizing and mildew-proof wall cloth and preparation method thereof
CN113290952A